Detection of Salmonella spp. in veterinary samples by combining selective enrichment and real-time PCR. (November 2017) - Goodman, Laura B.; McDonough, Patrick L.; Anderson, Renee R.; Franklin-Guild, Rebecca J.; Ryan, James R.; Perkins, Gillian A.; Thachil, Anil J.; Glaser, Amy L.; Thompson, Belinda S.
Rapid screening for enteric bacterial pathogens in clinical environments is essential for biosecurity. Salmonella found in veterinary hospitals, particularly Salmonella enterica serovar Dublin, can pose unique challenges for culture and testing because of its poor growth. Multiple Salmonella serovars including Dublin are emerging threats to public health given increasing prevalence and antimicrobial resistance. We adapted an automated food testing method to veterinary samples and evaluated the performance of the method in a variety of matrices including environmental samples ( n = 81), tissues ( n = 52), feces ( n = 148), and feed ( n = 29). A commercial kit was chosen as the basis for this approach in view of extensive performance characterizations published by multiple independent organizations. A workflow was established for efficiently and accurately testing veterinary matrices and environmental samples by use of real-time PCR after selective enrichment in Rappaport–Vassiliadis soya (RVS) medium. Using this method, the detection limit for S . Dublin improved by 100-fold over subculture on selective agars (eosin–methylene blue, brilliant green, and xylose–lysine–deoxycholate). Overall, the procedure was effective in detecting Salmonella spp. and provided next-day results.